2014
DOI: 10.1002/hup.2398
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular pharmacodynamics of donepezil hydrochloride on the PR and QT intervals in patients with dementia

Abstract: Care should be taken when administering donepezil to patients with atrioventricular block, or patients taking other drugs that can prolong the PR interval. Copyright © 2014 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…After excluding 4,324 papers after title and abstract review, 264 full‐text articles were examined, and 31 studies were \ included in the systematic review with meta‐analysis (22 longitudinal studies without a control group; 9 cohort studies with a control group) (Supplementary Figure S1). Seven of those were open‐label studies . The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After excluding 4,324 papers after title and abstract review, 264 full‐text articles were examined, and 31 studies were \ included in the systematic review with meta‐analysis (22 longitudinal studies without a control group; 9 cohort studies with a control group) (Supplementary Figure S1). Seven of those were open‐label studies . The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of those were open-label studies. [20][21][22][23][24]33,37 The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results could not reflect the pervasive impact of donepezil intervention because some cases had specific disease backgrounds such as unknown sinus sick syndrome, paroxysmal atrial fibrillation, myocardial infarction, or combination therapy with negative chronotropic drugs [ 27 , 31 ]. On the contrary, Isik and Igeta [ 32 , 33 ] reported that donepezil administration did not change QT and QTc interval in patients with AD compared with baseline. In the present study, no significant difference in QT, QTc, QTd, and T peak-end interval was detected after 4 weeks of donepezil intervention.…”
Section: Discussionmentioning
confidence: 99%